INTERDISCIPLINARY INTERACTION BETWEEN ARCHITECTS AND MECHANICAL ENGINEERS IN FORMING A COMPREHENSIVE APPROACH TO DESIGN - Василишин, Віталій; Василишин, Ольга; Довгань, Софія (SWorldJournal, 2025)
The article examines the issue of interdisciplinary interaction between architects and mechanical engineers as a fundamental basis for developing a comprehensive approach to modern design. It is determined that the synergy between architectural thinking a